Influence of Intrinsic and Extrinsic Characteristics of Detergents on Preferences of Female Employees of Selected Public Universities in Nigeria - Akeke, Niyi Israel; Mukolu, Maureen Obi (Archives of Business Research, 2018)
This study examined the influence of intrinsic and extrinsic characteristics of detergents on consumer preferences of female employee consumers. The study was carried out in Federal, and State universities located in Osun, Ogun, Lagos, Ondo, Oyo and Ekiti States of Southwest Nigeria. A total of 888 female employees in the selected institutions were sampled using two-stage sampling technique. Data were collected using a structured questionnaire. The data collected covered information on specific attributes and characteristics of detergents. Data collected was analysed using descriptive statistics, discrete choice model. Results showed that functional value of detergents and risk of use was the intrinsic characteristics of detergents influencing consumer preferences among female employees in public institutions. Extrinsic characteristics influencing consumer preference were price. The study concluded that consumer preference for detergents among female employees in selected public institutions in Southwest Nigeria is determined by hosts of factors which include brand, quality, intrinsic and extrinsic characteristics of detergents. It was thus recommended that business managers should link up with manufacturers of detergents to pay greater attention to intrinsic and extrinsic values of their products. Finally managers should enhance trust and reduce perceptions of risk associated with using available brands by promoting the quality and reliability of their retail brands.